2019
DOI: 10.1186/s12902-019-0387-y
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibitors in T2D and associated comorbidities — differentiating within the class

Abstract: Background: For patients with type 2 diabetes (T2D), cardiovascular disease (CVD) is the single most common cause of mortality. In 2008 and 2012, the Federal Drug Administration (FDA) and the European Medicines Agency (EMA) respectively mandated cardiovascular outcomes trials (CVOTs) on all new anti-diabetic agents, as prospective trials statistically powered to rule out excess cardiovascular risk in patients with T2D. Unexpectedly, some of these CVOTs have demonstrated not only cardiovascular safety, but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 67 publications
0
14
0
1
Order By: Relevance
“…Other secondary and exploratory outcomes in CVOTs have also suggested additional benefits of SGLT2i and GLP-1 RA that may be of particular relevance to patients with CVD, including slowed progression of albuminuria [ 39 , 40 ], and reductions in blood pressure and body weight [ 13 , 32 ]. For SGLT2i, CVOTs and other studies have consistently pointed to strong protection from renal function decline compared with placebo [ 10 , 12 , 38 ].…”
Section: Out Of Step With the Evidence: The Cvot-shaped Hole In Diabementioning
confidence: 99%
“…Other secondary and exploratory outcomes in CVOTs have also suggested additional benefits of SGLT2i and GLP-1 RA that may be of particular relevance to patients with CVD, including slowed progression of albuminuria [ 39 , 40 ], and reductions in blood pressure and body weight [ 13 , 32 ]. For SGLT2i, CVOTs and other studies have consistently pointed to strong protection from renal function decline compared with placebo [ 10 , 12 , 38 ].…”
Section: Out Of Step With the Evidence: The Cvot-shaped Hole In Diabementioning
confidence: 99%
“…This comprehensive safety analysis of a large pool of patients with advanced CKD who received empagliflozin in clinical trials found no overall differences in rates of SAEs, AEs leading to discontinuation, or events of special interest with empagliflozin treatment versus placebo, irrespective of baseline eGFR. An exception was genital infections, a well-recognized adverse effect of the SGLT2 inhibitor class ( 16 18 ), which occurred more frequently in the empagliflozin group versus the placebo group but with lower incidence rates in advanced CKD categories. This could be due to, at least in part, lesser urinary glucose excretion at lower levels of eGFR ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the applicability of SGLT2i is certainly much wider than the strict entry criteria of CVOTs, as shown in several of studies and subanalyses reporting the additional benefits of SGLT2i, particularly in chronic kidney disease and heart failure [40]. For instance, real-world evidence (RWE) studies have also confirmed reductions in mortality (43% to 49%) and hospitalization for heart failure (40% to 51%) in hundreds of thousands of patients [40]. So far, the main RWE studies published are CVD-Real, CVD-Real 2, EASEL, and EMPRISE; these studies compared SGLT2i with other antidiabetic drugs, especially against DPP-4 inhibitors (CVD-Real 2 and EMPRISE).…”
Section: Discussionmentioning
confidence: 99%